KOMBINASI LATIHAN EKSENTRIK M.GASTROCNEMIUS DAN LATIHAN PLYOMETRIC LEBIH BAIK DARI PADA LATIHAN EKSENTRIK M.QUADRICEPS DAN LATIHAN PLYOMETRIC TERHADAP PENINGKATAN AGILITY PADA MAHASISWA DI UNIVERSITAS ESA UNGGUL - Anggita, Miranti Yolanda; Purnawati, Susy; Lesmana, Indra (Sport and Fitness Journal; Volume 3, No.2, 2015)
Increase agility for students is determined by muscular strength, speed, and flexibility. The ability of muscles to contract quickly will increase the speed of muscle in motion. Increase in speed, strength and flexibility of muscles due to stretch muscle-tendinous unit. The mechanism become the basis for moving in the shortest possible time. Agility on student issues has not received much attention, the attention of the agility found better in many athletes. This research is an experimental study to analysis at the difference between the intervention of with gastrocmineus muscle eccentric exercises and plyometric exercises with eccentric exercise quadriceps muscle and plyometric to increase agility on students at the University of Esa Unggul. A total of 40 students aged 18-21 years old who meet the criteria inclusion were randomly divided into 2 treatment groups. The old treatment group I was given quadriceps muscle eccentric and plyometric treatment group II eccentric exercise gastrocmineus muscle and plyometric exercises. Both exercise was done 3 times was given per week for 6 weeks. Agility is measured by Right-Boomerang Run Test. The results of the hypothesis testing using t-test related and different mean values obtained agility treatment group I (16,43±0.89secon) and a second treatment group (16,01± 1,04secon)with p?0.05. Conclusion of the study is a combination of eccentric exercise m.gastrocnemius with plyometric exercise no better than the m.quadriceps eceentric exercises with plyometric exercises to increase agility on student at Esa Unggul University.
Keywords: agility, gasrtocmineus muscle eccentric exercise, exercise quadriceps eccentric, plyometric exercises.